Optical glass
By rationally preparing ingredients such as SiO2, B2O3, ZrO2, La2O3+Y2O3+Gd2O3 and other components in optical glass, the weather resistance and hardness of optical glass are improved, and the problem of insufficient weather resistance in the field of vehicle-mounted and monitoring security is solved. Extend service life.
Patent Information
- Application Number
- CN202411335327.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-26
- Publication Date
- 2024-12-27
AI Technical Summary
Existing optical glass lacks excellent weather resistance and high hardness in the field of on-board and monitoring and security, and is difficult to withstand the wear of sand and stone and the changes in harsh environment, resulting in a short service life.
Optical glass with specific component ratios is adopted, containing SiO2, B2O3, ZrO2, La2O3+Y2O3+Gd2O3, Ta2O5 and other components, with a refractive index of 1.78~1.85 and an Abbe number of 43~50. The weather resistance is improved through reasonable component design and hardness.
It achieves excellent weather resistance and high hardness of optical glass, extends its service life, and is suitable for on-board imaging, monitoring and security and other fields.
Smart Images

Figure BDA0005058099220000111 
Figure BDA0005058099220000121 
Figure BDA0005058099220000141
Abstract
Description
[0001] This application is a divisional application for the invention patent application with application number 202211038585.7, application date August 26, 2022, and name “Optical Glass”. Technical Field
[0002] The invention relates to an optical glass, in particular to an optical glass with excellent weather resistance and high hardness, and a glass preform, an optical element and an optical instrument made of the optical glass. Background Art
[0003] Optical glass is a glass material used to manufacture lenses, prisms, reflectors and windows in optical instruments. Optical glass with a refractive index of 1.78-1.85 and an Abbe number of 43-50 is widely used in the manufacture of optical instruments such as cameras, telescopes and microscopes due to its high refractive index. With the advancement of science and technology, digital products are constantly updated, the demand for optical glass is increasing, and higher requirements are also placed on the performance of optical glass. Optical glass with a refractive index of 1.78-1.86 and an Abbe number of 42-50 is of great significance in simplifying optical systems and improving imaging quality in the fields of optical design and optical communications. At present, optical glass that meets this optical performance can be used in the fields of vehicle-mounted, monitoring and security, but the optical glass used in this field needs to have high hardness and excellent weather resistance to resist the wear of sand and stones during vehicle driving, as well as changes in harsh environments, and extend the service life of the optical glass. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an optical glass with excellent weather resistance and high hardness.
[0005] The technical solution adopted by the present invention to solve the technical problem is:
[0006] (1) Optical glass, the components of which, expressed in percentage by weight, contain: SiO2: 3-20%; B2O3: 10-25%; ZrO2: 2-15%; La2O3+Y2O3+Gd2O3: 45-75%; Ta2O5: 0-10%, wherein (B2O3+Gd2O3+Ta2O5) / SiO2 is 0.8-8.0.
[0007] (2) The optical glass according to (1), wherein the components, expressed in weight percentage, further contain: Nb2O5: 0-5%; and / or TiO2: 0-5%; and / or RO: 0-8%; and / or Rn2O: 0-8%; and / or WO3: 0-5%; and / or ZnO: 0-8%; and / or Al2O3: 0-8%; and / or Yb2O3: 0-8%; and / or GeO2: 0-5%; and / or a clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
[0008] (3) Optical glass containing SiO2, B2O3, and ZrO2, wherein the composition, expressed in weight percentage, comprises: La2O3+Y2O3+Gd2O3: 45-75%, Ta2O5: 0-10%, wherein (B2O3+Gd2O3+Ta2O5) / SiO2 is 0.8-8.0, and the refractive index of the optical glass is n d is 1.78~1.85, Abbe number v d 43~50, Knoop hardness H K 690×10 7 Pa or above, and weather resistance CR is 2 or above.
[0009] (4) The optical glass according to (3), wherein the components, expressed in weight percentage, are: SiO2: 3-20%; and / or B2O3: 10-25%; and / or ZrO2: 2-15%; and / or Nb2O5: 0-5%; and / or TiO2: 0-5%; and / or RO: 0-8%; and / or Rn2O: 0-8%; and / or WO3: 0-5%; and / or ZnO: 0-8%; and / or Al2O3: 0-8%; and / or Yb2O3: 0-8%; and / or GeO2: 0-5%; and / or a clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
[0010] (5) The optical glass according to any one of (1) to (4), wherein the composition is expressed in weight percentage, wherein: (Gd2O3+Ta2O5) / Y2O3 is less than 1.5, preferably (Gd2O3+Ta2O5) / Y2O3 is 0.05 to 1.0, more preferably (Gd2O3+Ta2O5) / Y2O3 is 0.1 to 0.8, and further preferably (Gd2O3+Ta2O5) / Y2O3 is 0.1 to 0.6; and / or (B2O3+Gd2O3+Ta2O5) / Y2O3 is 0. ) / SiO2 is 1.0~6.0, preferably (B2O3+Gd2O3+Ta2O5) / SiO2 is 1.5~5.0, and more preferably (B2O3+Gd2O3+Ta2O5) / SiO2 is 1.5~3.5; and / or Ta2O5 / B2O3 is below 0.85, preferably Ta2O5 / B2O3 is 0.05~0.7, more preferably Ta2O5 / B2O3 is 0.1~0.6, and further preferably Ta2O5 / B2O3 is 0.15~0.5.
[0011] (6) The optical glass according to any one of (1) to (4), wherein the components are expressed in weight percentage, wherein: (Gd2O3+ZnO) / Y2O3 is less than 1.0, preferably (Gd2O3+ZnO) / Y2O3 is less than 0.8, more preferably (Gd2O3+ZnO) / Y2O3 is less than 0.6, and further preferably (Gd2O3+ZnO) / Y2O3 is less than 0.4; and / or SiO2 / (B2O3+N b2O5) is 0.15 to 1.5, preferably SiO2 / (B2O3 + Nb2O5) is 0.2 to 1.0, more preferably SiO2 / (B2O3 + Nb2O5) is 0.2 to 0.8, and further preferably SiO2 / (B2O3 + Nb2O5) is 0.25 to 0.65; and / or Y2O3 / (B2O3 + Nb2O5) is 0.3 to 2.0, preferably Y2O3 / (B2O3 + Nb2O5) is 0 .4 to 1.8, more preferably Y2O3 / (B2O3+Nb2O5) is 0.5 to 1.5, and further preferably Y2O3 / (B2O3+Nb2O5) is 0.6 to 1.2; and / or (Al2O3+Gd2O3) / ZrO2 is 2.5 or less, preferably (Al2O3+Gd2O3) / ZrO2 is 2.0 or less, more preferably (Al2O3+Gd2O3) / ZrO2 is 1.5 or less, and further preferably Select (Al2O3+Gd2O3) / ZrO2 to be less than 1.0; and / or (TiO2+WO3+Nb2O5) / Ta2O5 to be less than 1.5, preferably (TiO2+WO3+Nb2O5) / Ta2O5 to be less than 1.0, more preferably (TiO2+WO3+Nb2O5) / Ta2O5 to be less than 0.8, and further preferably (TiO2+WO3+Nb2O5) / Ta2O5 to be less than 0.5.
[0012] (7) The optical glass according to any one of (1) to (4), wherein the components are expressed in weight percentage, wherein: SiO2: 4-15%, preferably SiO2: 5-12%; and / or B2O3: 12-22%, preferably B2O3: 14-20%; and / or La2O3+Y2O3+Gd2O3: 50-75%, preferably La2O3+Y2O3+Gd2O3: 55-70%, more preferably La2O3+Y2O3+Gd2O3: 60-70%; and / or ZrO2: 3-12%, preferably ZrO2: 4-10%; and / or Nb2O5: 0-3%, preferably Nb2O5: 0-2%; and / or Ta2O5: 2-8%, preferably Ta2O5: 3-6%; and / or TiO2: 0-3%, preferably TiO2: 0-2%; and / or or RO: 0-3%, preferably RO: 0-2%; and / or Rn2O: 0-3%, preferably Rn2O: 0-2%; and / or WO3: 0-3%, preferably WO3: 0-2%; and / or ZnO: 0-4%, preferably ZnO: 0-2%; and / or Al2O3: 0-4%, preferably Al2O3: 0-2%; and / or Yb2O3: 0-5%, preferably Yb2O3: 0-3%; and / or GeO2: 0-3%, preferably GeO2: 0-1%; and / or clarifier: 0-1%, preferably clarifier: 0-0.5%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
[0013] (8) The optical glass according to any one of (1) to (4), wherein the components are expressed in weight percentage, wherein: La2O3: 35-65%, preferably La2O3: 40-60%, more preferably La2O3: 42-55%; and / or Y2O3: 5-30%, preferably Y2O3: 6-25%, more preferably Y2O3: 8-22%, further preferably Y2O3: 11-22%; and / or Gd2O3: 0-10%, preferably Gd2O3: 0-8%, more preferably Gd2O3: 0-5%, further preferably Gd2O3: 0-3%.
[0014] (9) The optical glass according to any one of (1) to (4), which does not contain WO3; and / or does not contain TiO2; and / or does not contain RO; and / or does not contain Rn2O; and / or does not contain ZnO; and / or does not contain Al2O3; and / or does not contain GeO2, wherein RO is one or more of MgO, CaO, SrO, and BaO, and Rn2O is one or more of Li2O, Na2O, and K2O.
[0015] (10) The optical glass according to any one of (1) to (4), wherein the refractive index n d is 1.78 to 1.85, preferably 1.79 to 1.84, more preferably 1.80 to 1.83, and further preferably 1.81 to 1.83. The Abbe number v d It is 43-50, preferably 44-49, more preferably 45-48.
[0016] (11) The optical glass according to any one of (1) to (4), wherein the density ρ of the optical glass is 5.10 g / cm 3 Below, preferably 5.00 g / cm 3 Below, more preferably 4.90g / cm 3 Below; and / or thermal expansion coefficient α -30 / 70℃ 85×10 -7 / K or less, preferably 80×10 -7 / K or less, more preferably 75×10 -7 / K or less, more preferably 70×10 -7 / K or less; and / or water resistance stability D W Two or more types, preferably one type; and / or 80 410nm or less, preferably λ 80 400nm or less, preferably λ 80 395nm or less; and / or λ5 is 325nm or less, preferably λ5 is 315nm or less, more preferably λ5 is 310nm or less; and / or weather resistance CR is 2 or more, preferably 1; and / or Knoop hardness H K 690×10 7 Pa or more, preferably 700×10 7 Pa or more, more preferably 710×10 7 Pa or more; and / or Young's modulus E is 10500×10 7 Pa~14000×10 7 Pa, preferably 11000×10 7 Pa~13500×10 7 Pa, more preferably 11500×10 7 Pa~13000×10 7 Pa; and / or wear rate F A The foaming degree is 100 to 150, preferably 105 to 145, more preferably 110 to 140, and further preferably 115 to 135; and / or the foaming degree is A grade or higher, preferably A0 grade or higher, and more preferably A 00 class.
[0017] (12) A glass preform made of the optical glass described in any one of (1) to (11).
[0018] (13) An optical element is made of the optical glass described in any one of (1) to (11), or is made of the glass preform described in (12).
[0019] (14) An optical instrument comprising the optical glass described in any one of (1) to (11) and / or the optical element described in (13).
[0020] The beneficial effects of the present invention are as follows: through reasonable component design, the optical glass of the present invention has excellent weather resistance and high hardness, and is suitable for the fields of vehicle-mounted imaging, monitoring and security. DETAILED DESCRIPTION
[0021] Below, the embodiment of the optical glass of the present invention is described in detail, but the present invention is not limited to the following embodiment, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of description for the repeated description part, the main purpose of the invention will not be limited thereby. In the following content, the optical glass of the present invention is sometimes referred to as optical glass or glass.
[0022] [Optical glass]
[0023] The following is an explanation of the range of each component (ingredient) of the optical glass of the present invention. In the present invention, unless otherwise specified, the content and total content of each component are all expressed in weight percentage (wt%), that is, the content and total content of each component are expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when the oxides, complex salts and hydroxides used as raw materials for the optical glass components of the present invention decompose and transform into oxides during melting, the total amount of the oxide material is taken as 100%.
[0024] Unless otherwise specified in specific circumstances, the numerical ranges listed in the present invention include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0025] <Essential Components and Optional Components>
[0026] SiO2 is the skeleton of optical glass. As a glass network generator, it has the effect of maintaining the chemical stability of glass and improving the resistance of glass to devitrification. In the present invention, the above effect is obtained by containing more than 3% SiO2. Preferably, the content of SiO2 is more than 4%, and more preferably, the content of SiO2 is more than 5%. If the content of SiO2 is higher than 20%, the glass meltability decreases and the transition temperature rises. Therefore, the upper limit of the content of SiO2 is 20%, preferably 15%, and more preferably 12%.
[0027] B2O3 is a component that forms the glass network structure. In the present invention, more than 10% of B2O3 is contained to maintain the stability of the glass, improve the melting property and resistance to devitrification of the glass, and preferably the content of B2O3 is more than 12%, and more preferably the content of B2O3 is more than 14%. However, when the content of B2O3 exceeds 25%, the chemical stability of the glass decreases, and the refractive index decreases. Therefore, the upper limit of the content of B2O3 in the present invention is 25%, preferably 22%, and more preferably 20%.
[0028] La2O3 is an effective component for increasing the refractive index of glass, and has a significant effect on improving the chemical stability and resistance to devitrification of glass. If its content is less than 35%, it is difficult to achieve the required optical constants; if the content is higher than 65%, the devitrification tendency of the glass increases and the thermal stability deteriorates. Therefore, the content of La2O3 is 35-65%, preferably 40-60%, and more preferably 42-55%.
[0029] Y2O3 can improve the refractive index and devitrification resistance of glass while maintaining low dispersibility, and adjust the Young's modulus of glass. The present invention achieves the above effects by containing more than 5% Y2O3; if its content exceeds 30%, the chemical stability and weather resistance of glass deteriorate. Therefore, the content of Y2O3 in the present invention is 5-30%, preferably 6-25%, more preferably 8-22%, and further preferably 11-22%.
[0030] Gd2O3 can improve the refractive index and chemical stability of glass, but if its content is higher than 10%, the devitrification resistance and abrasion resistance of glass deteriorate. Therefore, the content of Gd2O3 is 0 to 10%, preferably 0 to 8%, more preferably 0 to 5%, and further preferably 0 to 3%.
[0031] In some embodiments, by controlling the total content of La2O3, Y2O3 and Gd2O3 La2O3+Y2O3+Gd2O3 within the range of 45-75%, the glass is more likely to obtain a desired refractive index and Abbe number, and optimize the devitrification resistance and weather resistance of the glass. Therefore, preferably La2O3+Y2O3+Gd2O3 is 45-75%, more preferably La2O3+Y2O3+Gd2O3 is 50-75%, further preferably La2O3+Y2O3+Gd2O3 is 55-70%, and further preferably La2O3+Y2O3+Gd2O3 is 60-70%.
[0032] Yb2O3 is also a component that gives glass high refractive and low dispersion properties. If its content exceeds 8%, the anti-crystallization performance of the glass decreases. Therefore, the content of Yb2O3 is 0-8%, preferably 0-5%, more preferably 0-3%, and more preferably no Yb2O3 is contained.
[0033] ZrO2 can improve the viscosity, hardness, refractive index and chemical stability of optical glass, and can also reduce the thermal expansion coefficient of glass; when the content of ZrO2 is too high, the resistance to devitrification of glass decreases, the difficulty of melting increases, the melting temperature rises, and inclusions appear inside the glass and the light transmittance decreases. Therefore, the content of ZrO2 in the present invention is 2-15%, preferably 3-12%, and more preferably 4-10%.
[0034] TiO2 can increase the refractive index of glass, but too high a content will greatly reduce the dispersion coefficient and increase the tendency of crystallization, and even cause the glass to be significantly colored. Therefore, the TiO2 content is limited to 0-5%, preferably 0-3%, and more preferably 0-2%. In some embodiments, it is further preferred that no TiO2 is contained.
[0035] Ta2O5 has the effect of increasing the refractive index and improving the devitrification resistance of glass, but if its content is too high, the thermal stability of the glass will decrease, the density will increase, and the optical constants will be difficult to control within the desired range; on the other hand, compared with other components, the price of Ta2O5 is very expensive. From the perspective of practicality and cost, its usage should be minimized. Therefore, the content of Ta2O5 in the present invention is limited to 0-10%, preferably 2-8%, and more preferably 3-6%.
[0036] In some embodiments, the ratio of Ta2O5 to B2O3, Ta2O5 / B2O3, is controlled to be below 0.85, which can improve the chemical stability and devitrification resistance of the glass. Therefore, it is preferred that Ta2O5 / B2O3 is below 0.85. Furthermore, by controlling Ta2O5 / B2O3 within the range of 0.05 to 0.7, the weather resistance and abrasion resistance of the glass can be further optimized. Therefore, it is more preferred that Ta2O5 / B2O3 is 0.05 to 0.7, further preferred that Ta2O5 / B2O3 is 0.1 to 0.6, and further preferred that Ta2O5 / B2O3 is 0.15 to 0.5.
[0037] In some embodiments, the ratio (Gd2O3+Ta2O5) / Y2O3 between the total content of Gd2O3 and Ta2O5 Gd2O3+Ta2O5 and the content of Y2O3 is controlled to be below 1.5, which is beneficial for the glass to obtain a suitable abrasiveness and prevent the chemical stability of the glass from deteriorating. Therefore, it is preferred that (Gd2O3+Ta2O5) / Y2O3 is below 1.5. Furthermore, by controlling (Gd2O3+Ta2O5) / Y2O3 in the range of 0.05 to 1.0, the density and Young's modulus of the glass can be further optimized. Therefore, it is more preferred that (Gd2O3+Ta2O5) / Y2O3 is 0.05 to 1.0, further preferred that (Gd2O3+Ta2O5) / Y2O3 is 0.1 to 0.8, and further preferred that (Gd2O3+Ta2O5) / Y2O3 is 0.1 to 0.6.
[0038] In some embodiments, the ratio of the total content of B2O3, Gd2O3, and Ta2O5 (B2O3+Gd2O3+Ta2O5) to the content of SiO2 (B2O3+Gd2O3+Ta2O5) / SiO2 is controlled within the range of 0.8 to 8.0, which can improve the hardness of the glass and prevent the deterioration of the weather resistance of the glass. Therefore, it is preferred that (B2O3+Gd2O3+Ta2O5) / SiO2 is 0.8 to 8.0, and it is more preferred that (B2O3+Gd2O3+Ta2O5) / SiO2 is 1.0 to 6.0. Furthermore, by controlling (B2O3+Gd2O3+Ta2O5) / SiO2 within the range of 1.5 to 5.0, the bubble degree and thermal expansion coefficient of the glass can be further optimized. Therefore, it is further preferred that (B2O3+Gd2O3+Ta2O5) / SiO2 is 1.5 to 5.0, and it is further preferred that (B2O3+Gd2O3+Ta2O5) / SiO2 is 1.5 to 3.5.
[0039] Nb2O5 can increase the refractive index of glass, improve the chemical stability and resistance to devitrification of glass, but if its content is too large, the dispersion of the glass will increase, and it will be difficult to obtain glass with target optical constants. At the same time, the cost and density of the glass will increase, and the short-wave transmittance in the visible light region will decrease. Therefore, the content of Nb2O5 in the present invention is less than 5%, preferably less than 3%, and more preferably less than 2%.
[0040] In some embodiments, the ratio of SiO2 content to the total content of B2O3 and Nb2O5 B2O3 + Nb2O5, SiO2 / (B2O3 + Nb2O5), is controlled within the range of 0.15 to 1.5, which can improve the hardness and light transmittance of the glass. Therefore, preferably SiO2 / (B2O3 + Nb2O5) is 0.15 to 1.5, and more preferably SiO2 / (B2O3 + Nb2O5) is 0.2 to 1.0. Furthermore, by controlling SiO2 / (B2O3 + Nb2O5) within the range of 0.2 to 0.8, the thermal expansion coefficient and Young's modulus of the glass can be further optimized. Therefore, it is further preferred that SiO2 / (B2O3 + Nb2O5) is 0.2 to 0.8, and it is further preferred that SiO2 / (B2O3 + Nb2O5) is 0.25 to 0.65.
[0041] In some embodiments, the ratio of the content of Y2O3 to the total content of B2O3 and Nb2O5 (B2O3+Nb2O5) Y2O3 / (B2O3+Nb2O5) is controlled within the range of 0.3 to 2.0, which can improve the chemical stability of the glass, prevent the density of the glass from increasing, and optimize the abrasiveness of the glass. Therefore, preferably Y2O3 / (B2O3+Nb2O5) is 0.3 to 2.0, more preferably Y2O3 / (B2O3+Nb2O5) is 0.4 to 1.8, further preferably Y2O3 / (B2O3+Nb2O5) is 0.5 to 1.5, and further preferably Y2O3 / (B2O3+Nb2O5) is 0.6 to 1.2.
[0042] Alkaline earth metal oxide RO (RO is one or more of MgO, CaO, SrO, BaO) can adjust the optical constants of glass and optimize the chemical stability of glass, but when its content is high, the devitrification resistance of glass decreases. Therefore, the RO content is limited to 0-8%, preferably 0-3%, and more preferably 0-2%. In some embodiments, it is further preferred that RO is not contained.
[0043] Alkali metal oxide Rn2O (Rn2O is one or more of Li2O, Na2O, K2O) can reduce the transition temperature of glass, adjust the optical constants and high temperature viscosity of glass, and improve the melting property of glass, but when its content is high, the devitrification resistance and chemical stability of glass are reduced. Therefore, the content of Rn2O in the present invention is 0 to 8%, preferably 0 to 3%, and more preferably 0 to 2%. In some embodiments, it is further preferred that Rn2O is not contained.
[0044] WO3 can improve the refractive index and mechanical strength of glass. If the content of WO3 exceeds 5%, the thermal stability of glass decreases and the resistance to devitrification decreases. Therefore, the upper limit of WO3 content is 5%, preferably 3%, and more preferably 2%. In some embodiments, it is further preferred that WO3 is not contained.
[0045] In some embodiments, the ratio (TiO2+WO3+Nb2O5) / Ta2O5 between the total content of TiO2, WO3, and Nb2O5 and the content of Ta2O5 is controlled to be below 1.5, which can reduce the thermal expansion coefficient of the glass while preventing the light transmittance from decreasing. Therefore, it is preferred that (TiO2+WO3+Nb2O5) / Ta2O5 is below 1.5, and it is more preferred that (TiO2+WO3+Nb2O5) / Ta2O5 is below 1.0. Furthermore, by controlling (TiO2+WO3+Nb2O5) / Ta2O5 to be below 0.8, the bubble degree of the glass can be further optimized. Therefore, it is further preferred that (TiO2+WO3+Nb2O5) / Ta2O5 is below 0.8, and it is further preferred that (TiO2+WO3+Nb2O5) / Ta2O5 is below 0.5.
[0046] ZnO can adjust the refractive index and dispersion of glass, and reduce the high temperature viscosity and transition temperature of glass. If the content of ZnO is too high, the difficulty of glass molding increases and the anti-crystallization performance deteriorates. Therefore, the content of ZnO is 0 to 8%, preferably 0 to 4%, and more preferably 0 to 2%. In some embodiments, it is further preferred that ZnO is not contained.
[0047] In some embodiments, by controlling the ratio (Gd2O3+ZnO) / Y2O3 between the total content of Gd2O3 and ZnO Gd2O3+ZnO and the content of Y2O3 to be below 1.0, the thermal expansion coefficient of the glass can be reduced and the abrasiveness of the glass can be optimized. Therefore, it is preferred that (Gd2O3+ZnO) / Y2O3 is below 1.0, and it is more preferred that (Gd2O3+ZnO) / Y2O3 is below 0.8. Furthermore, controlling (Gd2O3+ZnO) / Y2O3 to be below 0.6 can make it easier for the glass to obtain a suitable Young's modulus and prevent the hardness of the glass from decreasing. Therefore, it is further preferred that (Gd2O3+ZnO) / Y2O3 is below 0.6, and it is further preferred that (Gd2O3+ZnO) / Y2O3 is below 0.4.
[0048] Al2O3 can improve the chemical stability of glass, but when its content exceeds 8%, the melting property and light transmittance of glass deteriorate. Therefore, the content of Al2O3 in the present invention is 0 to 8%, preferably 0 to 4%, and more preferably 0 to 2%. In some embodiments, it is further preferred that Al2O3 is not contained.
[0049] In some embodiments, the ratio of the total content of Al2O3 and Gd2O3 Al2O3 + Gd2O3 to the content of ZrO2 (Al2O3 + Gd2O3) / ZrO2 is controlled to be below 2.5, so that the glass can easily obtain a suitable abrasion resistance and Young's modulus, and prevent the light transmittance from decreasing. Therefore, it is preferred that (Al2O3 + Gd2O3) / ZrO2 is below 2.5, more preferably (Al2O3 + Gd2O3) / ZrO2 is below 2.0, further preferably (Al2O3 + Gd2O3) / ZrO2 is below 1.5, and further preferably (Al2O3 + Gd2O3) / ZrO2 is below 1.0.
[0050] GeO2 has the effect of increasing the refractive index and resistance to devitrification of glass, but if its content is too high, the chemical stability of the glass will decrease; on the other hand, compared with other components, GeO2 is very expensive, and its usage should be minimized from the perspective of practicality and cost. Therefore, the content of GeO2 in the present invention is limited to 0-5%, preferably 0-3%, more preferably 0-1%, and it is further preferred that GeO2 is not contained.
[0051] In the present invention, by containing 0-2% of one or more components of Sb2O3, SnO, SnO2, and CeO2 as a clarifier, the clarification effect of the glass can be improved and the bubble degree of the glass can be improved. The content of the clarifier is preferably 0-1%, and the content of the clarifier is more preferably 0-0.5%. When the content of Sb2O3 exceeds 2%, the clarification performance of the glass tends to decrease. At the same time, due to its strong oxidizing effect, the corrosion of the platinum or platinum alloy vessel for melting glass and the deterioration of the forming mold are promoted. Therefore, the content of Sb2O3 is preferably 0-2%, more preferably 0-1%, and further preferably 0-0.5%. SnO and SnO2 can also be used as clarifiers, but when their content exceeds 2%, the tendency of glass coloring increases, or when the glass is heated, softened, and molded again, Sn will become the starting point of crystal nucleation, resulting in a tendency of devitrification. Therefore, the content of SnO2 in the present invention is preferably 0-2%, more preferably 0-1%, and further preferably 0-0.5%; the content of SnO is preferably 0-2%, more preferably 0-1%, and further preferably 0-0.5%. The role and content ratio of CeO2 are consistent with those of SnO2, and its content is preferably 0-2%, more preferably 0-1%, and further preferably 0-0.5%, and further preferably CeO2 is not contained.
[0052] <Components that should not be contained>
[0053] In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo are contained alone or in combination in small amounts, the glass will be colored and absorption will occur at specific wavelengths in the visible light region, thereby weakening the property of the present invention of improving the visible light transmittance. Therefore, it is preferably substantially free of oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, especially for optical glasses that require transmittance at wavelengths in the visible light region.
[0054] The oxides of Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except for being inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can be manufactured, processed and discarded.
[0055] In order to achieve environmental friendliness, the optical glass of the present invention preferably does not contain As2O3 and PbO.
[0056] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in a small amount or trace amount in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.
[0057] Next, the properties of the optical glass of the present invention will be described.
[0058] <Refractive Index and Abbe Number>
[0059] The refractive index of optical glass (n d ) and the Abbe number (ν d ) Tested according to the method specified in GB / T 7962.1-2010.
[0060] In some embodiments, the refractive index (n d ) has a lower limit of 1.78, a preferred lower limit is 1.79, a more preferred lower limit is 1.80, and a further preferred lower limit is 1.81.
[0061] In some embodiments, the refractive index (n d ) has an upper limit of 1.85, a preferred upper limit of 1.84, and a more preferred upper limit of 1.83.
[0062] In some embodiments, the Abbe number (ν d ) has a lower limit of 43, a preferred lower limit of 44, and a more preferred lower limit of 45.
[0063] In some embodiments, the Abbe number (ν d ) has an upper limit of 50, a preferred upper limit of 49, and a more preferred upper limit of 48.
[0064] <density>
[0065] The density (ρ) of optical glass is tested according to the method specified in GB / T7962.20-2010.
[0066] In some embodiments, the density (ρ) of the optical glass of the present invention is 5.10 g / cm 3 Below, preferably 5.00 g / cm 3 Below, more preferably 4.90g / cm 3 the following.
[0067] <Coefficient of Thermal Expansion>
[0068] Thermal expansion coefficient of optical glass (α -30 / 70℃) The data at -30~70℃ were tested according to the method specified in GB / T7962.16-2010.
[0069] In some embodiments, the thermal expansion coefficient (α -30 / 70℃ ) is 85×10 -7 / K or less, preferably 80×10 -7 / K or less, more preferably 75×10 -7 / K or less, more preferably 70×10 -7 / K or less.
[0070] <Water resistance stability>
[0071] Water resistance stability of optical glass (D W ) (Powder method) Tested in accordance with the method specified in GB / T 17129.
[0072] In some embodiments, the water resistance stability (D W ) is 2 or more types, preferably 1 type.
[0073] <Color>
[0074] The short-wave transmission spectrum characteristics of the glass of the present invention are expressed by the coloration (λ 80 and λ5). 80 It refers to the wavelength when the glass transmittance reaches 80%. 80 The measurement is to use a glass with a thickness of 10±0.1mm and two opposite planes parallel to each other and optically polished, and measure the spectral transmittance in the wavelength range from 280nm to 700nm and the wavelength at which the transmittance is 80%. The so-called spectral transmittance or transmittance is the wavelength at which the incident intensity I is perpendicular to the above surface of the glass. in Light of intensity I passes through the glass and emerges from a plane out The light of the case through I out / I in The amount expressed by λ also includes the transmittance of the surface reflection loss on the above surfaces of the glass. The higher the refractive index of the glass, the greater the surface reflection loss. Therefore, in high refractive index glass, λ 80 A small value of means that the glass itself is less colored and has a high light transmittance.
[0075] In some embodiments, the λ of the optical glass of the present invention is 80 410nm or less, preferably λ 80 400nm or less, preferably λ 80 Below 395nm.
[0076] In some embodiments, the λ5 of the optical glass of the present invention is 325 nm or less, preferably 315 nm or less, and more preferably 310 nm or less.
[0077] <Weather resistance>
[0078] The test method for weather resistance (CR) of optical glass is as follows: place the sample in a test box with a saturated water vapor environment of 90% relative humidity, alternately cycle every 1 hour at 40-50°C, and cycle for 15 cycles. The weather resistance category is divided according to the change in turbidity before and after the sample is placed. The weather resistance classification is shown in Table 1:
[0079] Table 1.
[0080]
[0081] In some embodiments, the weather resistance (CR) of the optical glass of the present invention is Class 2 or higher, preferably Class 1.
[0082] <Knoop hardness>
[0083] Knoop hardness of optical glass (H K ) The test shall be carried out according to the test method specified in GB / T7962.18-2010.
[0084] In some embodiments, the Knoop hardness (H K ) is 690×10 7 Pa or more, preferably 700×10 7 Pa or more, more preferably 710×10 7 Pa or above.
[0085] <Young's modulus>
[0086] Young's modulus (E) is calculated using the following formula by ultrasonic testing of its longitudinal wave velocity and transverse wave velocity.
[0087]
[0088] G=V S 2 ρ
[0089] Where: E is Young's modulus, Pa;
[0090] G is the shear modulus, Pa;
[0091] V T is the shear wave velocity, m / s;
[0092] V S is the longitudinal wave velocity, m / s;
[0093] ρ is the glass density, g / cm 3 .
[0094] In some embodiments, the lower limit of the Young's modulus (E) of the optical glass of the present invention is 10500×10 7 Pa, the preferred lower limit is 11000×10 7 Pa, and the more preferred lower limit is 11500×10 7 Pa.
[0095] In some embodiments, the upper limit of the Young's modulus (E) of the optical glass of the present invention is 14000×10 7 Pa, the upper limit is preferably 13500×10 7 Pa, and the upper limit is more preferably 13000×10 7 Pa.
[0096] <Abrasion>
[0097] Abrasiveness of optical glass (F A ) refers to the value obtained by multiplying the ratio of the wear volume of the sample to the wear volume (volume) of the standard sample (H-K9 glass) under exactly the same conditions by 100, and is expressed by the following formula:
[0098] F A =V / V0×100=(W / ρ) / (W0 / ρ0)×100
[0099] Where: V—volume wear of the sample being tested;
[0100] V0—Volume loss of standard sample;
[0101] W—mass wear loss of the sample being tested;
[0102] W0—standard sample mass wear;
[0103] ρ—density of the sample being tested;
[0104] ρ0—standard sample density.
[0105] In some embodiments, the abrasiveness (F A ) has a lower limit of 100, a preferred lower limit of 105, a more preferred lower limit of 110, and a further preferred lower limit of 115.
[0106] In some embodiments, the abrasiveness (F A ) has an upper limit of 150, a preferred upper limit of 145, a more preferred upper limit of 140, and a further preferred upper limit of 135.
[0107] <Bubble Degree>
[0108] The bubble degree of optical glass is tested according to the method specified in GB / T7962.8-2010.
[0109] In some embodiments, the bubble degree of the optical glass of the present invention is above grade A, preferably above grade A0, and more preferably above grade A1. 00 class.
[0110] [Method for producing optical glass]
[0111] The manufacturing method of the optical glass of the present invention is as follows: the glass of the present invention is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, etc.), boric acid, etc. as raw materials, and after the ingredients are prepared according to the conventional method, the prepared furnace materials are put into a melting furnace (such as platinum or platinum alloy crucible) at 1200-1450°C for melting, and after clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.
[0112] [Glass preforms and optical components]
[0113] The prepared optical glass can be used to make a glass preform by means of direct drop molding, grinding, or compression molding such as hot press molding. That is, the molten optical glass can be directly precision drop molded into a glass precision preform, or the glass preform can be made by mechanical processing such as grinding and grinding, or the preform for compression molding made of the optical glass can be made by hot press molding and then grinding. It should be noted that the means for preparing the glass preform are not limited to the above means.
[0114] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferred to form a preform from the optical glass of the present invention and use the preform to perform re-hot pressing, precision stamping, etc. to produce optical elements such as lenses and prisms.
[0115] The glass preform and optical element of the present invention are both formed of the optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass; the optical element of the present invention has the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value.
[0116] Examples of the lens include various lenses having spherical or aspherical lens surfaces, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens.
[0117] [Optical instruments]
[0118] The optical element formed by the optical glass of the present invention can be used to manufacture optical instruments such as photographic equipment, video equipment, projection equipment, display equipment, vehicle-mounted equipment and monitoring equipment.
[0119] Example
[0120] <Optical Glass Example>
[0121] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided.
[0122] This embodiment adopts the above optical glass manufacturing method to obtain optical glasses having the compositions shown in Tables 2 to 4. In addition, the properties of each glass are measured by the testing method described in the present invention, and the measurement results are shown in Tables 2 to 4.
[0123] Table 2.
[0124]
[0125]
[0126] Table 3.
[0127]
[0128]
[0129] Table 4.
[0130]
[0131]
[0132]
[0133] <Glass Preform Example>
[0134] The glass obtained from optical glass examples 1 to 24# is used, for example, by grinding processing, or by molding methods such as hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.
[0135] <Optical Element Embodiment>
[0136] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the internal stress of the glass and fine-tune the refractive index so that the optical properties such as the refractive index reach the desired values.
[0137] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.
[0138] <Optical Instrument Embodiment>
[0139] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips.
Claims
1. Optical glass, characterized in that: Its components, expressed in weight percentage, include: SiO2: 4-20%; B2O3: 10-25%; ZrO2: 2-15%; La2O3+Y2O3+Gd2O3: 45-75%; Ta2O5: 0-8%, wherein (B2O3+Gd2O3+Ta2O5) / SiO2 is 0.8-8.
0.
2. The optical glass according to claim 1, characterized in that: Its components are expressed in weight percentage and further contain: Nb2O5: 0-5%; and / or TiO2: 0-5%; and / or RO: 0-8%; and / or Rn2O: 0-8%; and / or WO3: 0-5%; and / or ZnO: 0-8%; and / or Al2O3: 0-8%; and / or Yb2O3: 0-8%; and / or GeO2: 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
3. Optical glass, characterized in that: Contains SiO2, B2O3, and ZrO2. The components are expressed in weight percentage as follows: La2O3+Y2O3+Gd2O3: 45-75%, Ta2O5: 0-8%, wherein (B2O3+Gd2O3+Ta2O5) / SiO2 is 0.8-8.0, and the refractive index of the optical glass is n d is 1.78~1.85, Abbe number v d 43~50, Knoop hardness H K 690×10 7 Pa or above, and weather resistance CR is 2 or above.
4. The optical glass according to claim 3, characterized in that: Its components, expressed in weight percentage, contain: SiO2: 4-20%; and / or B2O3: 10-25%; and / or ZrO2: 2-15%; and / or Nb2O5: 0-5%; and / or TiO2: 0-5%; and / or RO: 0-8%; and / or Rn2O: 0-8%; and / or WO3: 0-5%; and / or ZnO: 0-8%; and / or Al2O3: 0-8%; and / or Yb2O3: 0-8%; and / or GeO2: 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
5. The optical glass according to any one of claims 1 to 4, characterized in that: The components are expressed in weight percentage, wherein: (Gd2O3+Ta2O5) / Y2O3 is less than 1.5, preferably (Gd2O3+Ta2O5) / Y2O3 is 0.05-1.0, more preferably (Gd2O3+Ta2O5) / Y2O3 is 0.1-0.8, and further preferably (Gd2O3+Ta2O5) / Y2O3 is 0.1-0.6; and / or (B2O3+Gd2O3+Ta2O5) / SiO2 is 1.0- 6.0, preferably (B2O3+Gd2O3+Ta2O5) / SiO2 is 1.5~5.0, more preferably (B2O3+Gd2O3+Ta2O5) / SiO2 is 1.5~3.5; and / or Ta2O5 / B2O3 is below 0.85, preferably Ta2O5 / B2O3 is 0.05~0.7, more preferably Ta2O5 / B2O3 is 0.1~0.6, and further preferably Ta2O5 / B2O3 is 0.15~0.
5.
6. The optical glass according to any one of claims 1 to 4, characterized in that: The components are expressed in weight percentage, wherein: (Gd2O3+ZnO) / Y2O3 is less than 1.0, preferably (Gd2O3+ZnO) / Y2O3 is less than 0.8, more preferably (Gd2O3+ZnO) / Y2O3 is less than 0.6, and further preferably (Gd2O3+ZnO) / Y2O3 is less than 0.4; and / or SiO2 / (B2O3+Nb2O5) is 0.15 to 1.5, preferably SiO2 / (B2O3+Nb2O5) is 0.2 to 1.0, more preferably SiO2 / (B2O3+Nb2O5) is 0.2 to 0.8, and further preferably SiO2 / (B2O3+Nb2O5) is 0.25 to 0.65; and / or Y2O3 / (B2O3+Nb2O5) is 0.3 to 2.0, preferably Y2O3 / (B2O3+Nb2O5) is 0.4 to 1.8, and more preferably Y 2O3 / (B2O3+Nb2O5) is 0.5 to 1.5, and more preferably Y2O3 / (B2O3+Nb2O5) is 0.6 to 1.2; and / or (Al2O3+Gd2O3) / ZrO2 is 2.5 or less, and preferably (Al2O3+Gd2O3) / ZrO2 is 2.0 or less, and more preferably (Al2O3+Gd2O3) / ZrO2 is 1.5 or less, and more preferably (Al2O3+Gd2O3) / ZrO2 is 1.5 or less, and more preferably (Al2O3+Gd2O3) / ZrO2 is 2.5 or less, and more preferably (Al2O3+Gd2O3) / ZrO2 is 2.0 or less, and more preferably (Al2O3+Gd2O3) / ZrO2 is 1.5 ... 3+Gd2O3) / ZrO2 is less than 1.0; and / or (TiO2+WO3+Nb2O5) / Ta2O5 is less than 1.5, preferably (TiO2+WO3+Nb2O5) / Ta2O5 is less than 1.0, more preferably (TiO2+WO3+Nb2O5) / Ta2O5 is less than 0.8, and further preferably (TiO2+WO3+Nb2O5) / Ta2O5 is less than 0.
5.
7. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, wherein: SiO2: 4-15%, preferably SiO2: 5-12%; and / or B2O3: 12-22%, preferably B2O3: 14-20%; and / or La2O3+Y2O3+Gd2O3: 50-75%, preferably La2O3+Y2O3+Gd2O3: 55-70%, more preferably La2O3+Y2O3+Gd2O3: 60-70%; and / or Z rO2: 3-12%, preferably ZrO2: 4-10%; and / or Nb2O5: 0-3%, preferably Nb2O5: 0-2%; and / or Ta2O5: 2-8%, preferably Ta2O5: 3-6%; and / or TiO2: 0-3%, preferably TiO2: 0-2%, more preferably no TiO2; and / or RO: 0-3%, preferably RO: 0-2%, more preferably no RO; and / or Rn2O: 0 ~3%, preferably Rn2O: 0~2%, more preferably no Rn2O; and / or WO3: 0~3%, preferably WO3: 0~2%, more preferably no WO3; and / or ZnO: 0~4%, preferably ZnO: 0~2%, more preferably no ZnO; and / or Al2O3: 0~4%, preferably Al2O3: 0~2%, more preferably no Al2O3; and / or Yb2O3: 0~5%, preferably Yb2O3: 0~3%; and / or GeO2: 0~3%, preferably GeO2: 0~1%, more preferably no GeO2; and / or clarifier: 0~1%, preferably clarifier: 0~0.5%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
8. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, among which: La2O3: 35-65%, preferably La2O3: 40-60%, more preferably La2O3: 42-55%; and / or Y2O3: 5-30%, preferably Y2O3: 6-25%, more preferably Y2O3: 8-22%, further preferably Y2O3: 11-22%; and / or Gd2O3: 0-10%, preferably Gd2O3: 0-8%, more preferably Gd2O3: 0-5%, further preferably Gd2O3: 0-3%.
9. The optical glass according to any one of claims 1 to 4, characterized in that: The refractive index n of the optical glass d is 1.78 to 1.85, preferably 1.79 to 1.84, more preferably 1.80 to 1.83, and further preferably 1.81 to 1.
83. The Abbe number v d It is 43-50, preferably 44-49, more preferably 45-48.
10. The optical glass according to any one of claims 1 to 4, characterized in that: The density of the optical glass is 5.10 g / cm 3 Below, preferably 5.00 g / cm 3 Below, more preferably 4.90g / cm 3 Below; and / or thermal expansion coefficient α -30 / 70℃ 85×10 -7 / K or less, preferably 80×10 -7 / K or less, more preferably 75×10 -7 / K or less, more preferably 70×10 -7 / K or less; and / or water resistance stability D W Two or more types, preferably one type; and / or 80 410nm or less, preferably λ 80 400nm or less, preferably λ 80 395nm or less; and / or λ5 is 325nm or less, preferably λ5 is 315nm or less, more preferably λ5 is 310nm or less; and / or weather resistance CR is 2 or more, preferably 1; and / or Knoop hardness H K 690×10 7 Pa or more, preferably 700×10 7 Pa or more, more preferably 710×10 7 Pa or more; and / or Young's modulus E is 10500×10 7 Pa~14000×10 7 Pa, preferably 11000×10 7 Pa~13500×10 7 Pa, more preferably 11500×10 7 Pa~13000×10 7 Pa; and / or wear rate F A The foaming degree is 100 to 150, preferably 105 to 145, more preferably 110 to 140, and further preferably 115 to 135; and / or the foaming degree is A grade or higher, preferably A0 grade or higher, and more preferably A 00 class.
11. A glass preform, characterized in that: Made of the optical glass described in any one of claims 1 to 10.
12. An optical element, characterized in that The optical glass is made of any one of claims 1 to 10, or the glass preform is made of claim 11.
13. An optical instrument, characterized in that Contains the optical glass according to any one of claims 1 to 10, and / or contains the optical element according to claim 12.
Citation Information
Patent Citations
Optical glass with high index of refraction
CN102050571A
Lanthanum flint optical glass and preparation method thereof
CN103395981A
Optical glass
CN105837028A
Dense lanthanum flint optical glass as well as preparation method and optical element thereof
CN107244803A
Glass, glass blank for press-forming, optical element blank, and optical element
CN108529871A
